The Influence of Participatory Leadership and Budget Transparency on Public Service Accountability with Community Involvement as an Intervening Variable - Nurmalasyiah (International Humanity Advance, Business & Sciences, 2025)
This study aims to analyze the influence of participatory leadership and budget transparency on public service accountability, with community involvement as an intervening variable. Using a quantitative approach with an explanatory design, data were collected through a questionnaire survey of local government officials, communities, and related stakeholders. Data analysis was conducted using Structural Equation Modeling (SEM). The results showed that participatory leadership and budget transparency had a significant effect on public service accountability, both directly and through community involvement. These findings emphasize the importance of community involvement in strengthening accountable governance and provide practical implications for public service reform in Indonesia.